EVALUATION OF SALINITY INTRUSION IN THE SOUTHWEST COASTAL ZONE OF VIETNAM - Kien, Nguyen Chinh; Manh, Dinh Van; Lai, Hoang Van (Vietnam Journal of Marine Science and Technology, 2014)
The Southwest sea of Vietnam, from Ca Mau cape to the Cambodian border, including Phu Quoc and Tho Chu islands, has been especially interested and played an important role in the socio-economic development and national security of Vietnam. Requirements for understanding natural conditions, especially hydrodynamical characteristics and the marine environment for construction, mining, protection and integrated management of this area is urgently needed. In recent years, there have been several investigations and researches within the framework of national research projects to provide an overview of the understanding or to solve specific problems in the area. However, the previous researches in details and concret, including complex changes of seabed topography, morphology shore, marine estuaries/channels were still not met the requirements. In this report, a linked 1-2D numerical model has been established to describe of the characteristics of tides, currents and evaluate of salinity intrusion through channel/river system of the southwest coastal region.